HUBUNGAN PENGETAHUAN IBU TENTANG PEMBERIAN NUTRISI YANG BAIK TERHADAP TUMBUH KEMBANG ANAK USIA 3-5 TAHUN DI POSYANDU MAWAR DUSUN GEDANGAN DESA JATIROYO JATIPURO KARANGANYAR - Dinar Ariasti; Andreas Wahyu Widianto; Lusiana Ambarningrum (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
AbstractIntroduction: Lack of nutrients in the diet can lead to disruption of the growth and development of infants. In addition, children become more susceptible to infection and subsequent disease can even lead to death of the baby. Therefore, it is necessary nutritional needs serious attention. The provision of adequate nutrition in children should begin in the womb, namely the provision of adequate nutrition in pregnant women. Mothers' knowledge of nutrition is very important for the growth and development of children.The purpose: Of this study was to determine the relationship of knowledge of good nutrition for growth and development of children in Gedangan Village Jatiroyo District of Jatipuro Karanganyar.The subjects: Were mothers with children under the age of 3-5 years in Gedangan Village Jatiroyo District of Jatipuro Karanganyar. Sampling is done with saturated sampling technique, namely by taking all members of the population being sampled because the population is small.Methods: In this study is a correlation study, case-control approach. Data were obtained by questionnaire and observation method KMS and DDST to observe growth and development in children aged 3-5 years. The data have been collected and analyzed with the chi square test with p = 0.05.The results: Of the study there were 19 mothers with a high level of knowledge about nutrition, growth and development of children according to age and 5 women with a high level of knowledge, growth and development of children is not appropriate and 6 women with moderate levels of knowledge about nutrition, growth and development of children are not age appropriate. After being tested by Chi-Square SPSS version 16.0 with Î± = 5% (0.05) of 0000 thus obtained p value of p <0.05, which means that Ho is rejected and Ha accepted.The conclusion: Of this study is that there is a relationship between maternal knowledge about good nutrition for growth and development of children aged 3-5 years in Posyandu Dusun Gedangan Desa JatiroyoKeywords: knowledge level, nutrition